AN EFFORTS TO INCREASE STUDENT’S KNOWLEDGE ABOUT THE IMPORTANCE OF CHOOSING HEALTHY SNACKS AT KRAGAN ELEMENTARY SCHOOL, SIDOARJO - Nima Eka Nur Rahmania; Nanda Ratri Nurwanti; Anastasya Hardyana Putri (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2023)
An increasing students' knowledge through health promotion at Kragan Elementary School, Sidoarjo is a form of counseling and practice that aims to provide education about the importance of healthy snacks so that it is hoped that students can choose healthy snacks that are beneficial for growth and health. Inaccuracy in choosing snacks can result in negative impacts on health such as obesity, decreased intelligence and diarrhea. The activity was held on January 26th, 2023 at Kragan Elementary School, Sidoarjo. The target was students in grades 4th, 5th and 6th at Kragan Elementary School, Sidoarjo. Before the implementation of the activity, there is a preparation process for the activity for 1 month before the activies are carried out, starting from the selection of health education materials to submitting permits to related parties. As an evaluation of the activity attended by 90 students, the participants participated in the activity enthusiastically and conductively, the activity could be carried out smoothly and on time.